2018
DOI: 10.1093/nar/gky641
|View full text |Cite
|
Sign up to set email alerts
|

Combined deficiency of Senataxin and DNA-PKcs causes DNA damage accumulation and neurodegeneration in spinal muscular atrophy

Abstract: Chronic low levels of survival motor neuron (SMN) protein cause spinal muscular atrophy (SMA). SMN is ubiquitously expressed, but the mechanisms underlying predominant neuron degeneration in SMA are poorly understood. We report that chronic low levels of SMN cause Senataxin (SETX)-deficiency, which results in increased RNA–DNA hybrids (R-loops) and DNA double-strand breaks (DSBs), and deficiency of DNA-activated protein kinase-catalytic subunit (DNA-PKcs), which impairs DSB repair. Consequently, DNA damage acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 78 publications
6
110
0
Order By: Relevance
“…Mediated by p38 MAPK SMN deficiency has been shown to activate several kinases (Wu et al, 2011;Genabai et al, 2015;Kannan et al, 2018;Miller et al, 2015;Ng et al, 2015), including p38 MAPK, which directly phosphorylates serine 18 of p53 (Toledo and Wahl, 2006;Vousden and Prives, 2009). We also found that pharmacological inhibition of p38 MAPK in SMA mice enhances motor function without increasing SMN expression (D.M.W and L.P., unpublished data).…”
Section: Stasimon-dependent P53 S18 Phosphorylation Ismentioning
confidence: 64%
See 1 more Smart Citation
“…Mediated by p38 MAPK SMN deficiency has been shown to activate several kinases (Wu et al, 2011;Genabai et al, 2015;Kannan et al, 2018;Miller et al, 2015;Ng et al, 2015), including p38 MAPK, which directly phosphorylates serine 18 of p53 (Toledo and Wahl, 2006;Vousden and Prives, 2009). We also found that pharmacological inhibition of p38 MAPK in SMA mice enhances motor function without increasing SMN expression (D.M.W and L.P., unpublished data).…”
Section: Stasimon-dependent P53 S18 Phosphorylation Ismentioning
confidence: 64%
“…Our findings that AAV9-STAS and p38 MAPK inhibition reduces phosphorylation of p53 S18 and rescues survival of SMA motor neurons in vivo, together with the observation that Stasimon deficiency is sufficient to induce p38 MAPK-mediated p53 S18 phosphorylation in vitro, fill this knowledge gap, placing Stasimon dysfunction upstream of a p38 MAPK/p53-dependent neurodegenerative axis (Figure 7). SMN deficiency induces the activation of several kinases that have been implicated in the degeneration of SMA motor neurons (Genabai et al, 2015;Kannan et al, 2018;Miller et al, 2015;Ng et al, 2015) and are known to phosphorylate p53 (Toledo and Wahl, 2006;Vousden and Prives, 2009), including the stressactivated protein kinases JNK and p38 MAPK (Genabai et al, 2015;Wu et al, 2011). It was recently suggested that loss of (C) ChAT immunostaining of P11 L5 spinal cords from the same groups as in (A).…”
Section: Discussionmentioning
confidence: 95%
“…In summary, our work identifies Stasimon as a key determinant of defective synaptic connectivity and function in the SMA sensory-motor circuit as well as an upstream trigger of a signaling cascade(s) that feeds into p53 and the motor neuron cell death pathway. SMN deficiency has previously been linked to the activation of several kinases implicated in the degeneration of SMA motor neurons (Genabai et al, 2015;Kannan et al, 2018;Miller et al, 2015;Ng et al, 2015) and known to phosphorylate p53 (Toledo and Wahl, 2006;Vousden and Prives, 2009). Identification of the Stasimon-dependent signal transduction pathways and kinase(s) that drive p53 phosphorylation and motor neuron death in SMA might reveal viable targets for the development of neuroprotective agents for SMA therapy.…”
Section: The Observation That Stasimon Restoration Suppresses Motor Nmentioning
confidence: 99%
“…A recent study showed that neuronal cells from SMA express only low levels of SETX and DNA-PKcs, a highly conserved NHEJ factor. As a result, SMA neurons display higher levels of R-loops that culminate DSB formation, and cellular toxicity [93]. Importantly, these phenotypic manifestations can be corrected by the overexpression of SETX.…”
Section: Dna Double-strand Break Repair and Replication Fork Stabilitymentioning
confidence: 99%